Adult retrospective report of child abuse and prospective indicators of childhood harm: a population birth cohort study - Snehal M. Pinto Pereira (BMC, 2021)
Abstract Background We aim to determine whether adult retrospective report of child abuse is associated with greater risk of prospectively assessed harmful environments in childhood. We assessed possible recall basis by adult depression status. Methods At 45 years, participants of the 1958 British birth cohort (N = 9308) reported a range of abuse types (by 16 years). Prospective data, ages 7–16 years, were obtained for impoverished upbringing, hazardous conditions, anti-social behaviours and 16 years poor parent-child relationships. We estimated associations between retrospective report of child abuse and prospectively measured harm using (i) odds ratios (ORs, 95% confidence intervals) and (ii) positive predictive values (PPVs). PPVs were calculated stratified by adult depression status. Results Prevalence of retrospectively reported abuse ranged from 10.7% (psychological) to 1.60% (sexual) and 14.8% reported ≥ 1 type; prospectively recorded harm ranged from 10% (hazardous conditions/poor parent-child relationships) to 20% (anti-social behaviours). Adults retrospectively reporting abuse were more likely to have had harmful childhood environments: 52.4% had ≥ 1 indicator of harm (vs. 35.6% among others); OR sex-adjusted for poor relationships with parents was 2.98 (2.50, 3.54). For retrospectively reported (vs. none) abuse, there was a trend of increasing relative risk ratio with number of harms, from 1.75 (1.50, 2.03) for 1 to 4.68 (3.39, 6.45) for 3/4 childhood harms. The PPV of ≥ 1 prospectively recorded harm did not differ between depressed (0.58 (0.52, 0.64)) and non-depressed (0.58 (0.55, 0.61)) groups. Conclusions In a population cohort, adult retrospective report of child abuse was associated with several harms, prospectively measured from childhood to adolescence, providing support for the validity of retrospective report-based research. Findings suggest retrospectively reported child abuse is not biased by depression in adulthood.